A retrospective study of the comparison of maternal outcomes in in-vitro-fertilization pregnancy versus spontaneous conception - Yadav, Reena; Chopra, Kanika; Goyal, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The adverse maternal outcomes of newer technology of IVF have not been studied so far, especially in India. The aim of the study was to compare maternal near miss and mortality between IVF-conceived and spontaneously conceived pregnancies, at a tertiary-level hospital, in Delhi. Methods: We conducted a retrospective cohort study from 2018-2020. The demographic, obstetrics, past history, obstetric-related morbidity, mode of delivery, details of maternal near miss and mortality, and their reasons were recorded. Similar data from spontaneous conceptions were compiled. Comparison of maternal characteristics was tested using chi-square test, p<0.05 was considered significant. Results: Mean age of women in the study group was 33.16±5.58 years and in controls was 26.16±4.28 years. The risk of multiple pregnancy (58.5% versus 2%, p<0.0001), pre-eclampsia (62.8% versus 17.1%, p<0.0001), gestational diabetes mellitus (23.5% versus 14.2%, p=0.0493), intrahepatic cholestasis of pregnancy (32.8% versus 10%, p<0.0001), antepartum haemorrhage (12.1% versus 2.85%, p=0.0066), preterm deliveries (66.4% versus 5.7%, <0.0001), and maternal near miss (12.8% versus 0.7%, OR 20.50, 95% CI-2.6979 to 155.8916, p=0.0035) were much higher in the study group as compared to the control group and was statistically significant. The odds of maternal mortality were 4.0882, 95% CI 0.4512 to 37.0465, p=0.2105 in the study group as compared to the control group. Conclusions: There is a need to counsel couples wanting to conceive with IVF about not just the procedure and success rates of it, but also the potential for pregnancy complications.